Penerapan Akuntansi Manajemen Lingkungan pada Rumah Makan Studi Kasus di Kota Gorontalo - Masnawaty Sangkala (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
The existence of environmental management accounting in an organization aims to provide information on the financial and non-financial aspects of the company's environmental performance. This study aims to determine the understanding of restaurant actors who have obligations. The status of the implementation of Environmental Management Efforts and Regular Environmental Monitoring of Business. The research method used is a qualitative method (post positivism) which is expected to be able to reveal answers to a field phenomenon inductively. Data collected based on triangulation with data analysis using the concept of Miles and Huberman (1994). The results of this study indicate that restaurant business actors' understanding of environmental management accounting information has an impact on financial reporting, especially environmental costs.